2013
DOI: 10.5812/jjm.7366
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of Drug- Resistant Mutants in Patients with Chronic HBV Infection After Lamivudine Treatment

Abstract: Background: Hepatitis B virus (HBV) is replicated through reverse transcription of polymerase gene. Lamivudine can postpone the clinical progression in Hepatitis B infected patients, but the long-term monotherapy causes the emerge of YMDD (tyrosine-methionine-aspartateaspartate), LLAQ (leucine-leucine-alanine-glutamine) motifs and increases the Alanine aminotransferase (ALT) and HBV DNA levels. Objectives: The aim of this study was to investigate rtL180M and rtM204V mutations in polymerase gene of HBV in infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Owing to the low fidelity of the virus polymerase, the high replication rate and under the treatment pressure, different mutations occur throughout the HBV genome ( 29 ). The results of mutations were similar to those of the previous studies reporting that the most common mutation affects the highly conserved YMDD motif, resulting in a methionine to valine or isoleucine substitution at codon 204 (M204V/I) and between them, M204I mutant is significantly more resistant to LAM than the M204V mutant ( 27 , 30 ). Also, the frequency of YMDD mutation in the current study subjects (46%) was approximately higher than those of the previously reported values of 27% ( 26 ) and 21% ( 31 ).…”
Section: Discussionsupporting
confidence: 88%
“…Owing to the low fidelity of the virus polymerase, the high replication rate and under the treatment pressure, different mutations occur throughout the HBV genome ( 29 ). The results of mutations were similar to those of the previous studies reporting that the most common mutation affects the highly conserved YMDD motif, resulting in a methionine to valine or isoleucine substitution at codon 204 (M204V/I) and between them, M204I mutant is significantly more resistant to LAM than the M204V mutant ( 27 , 30 ). Also, the frequency of YMDD mutation in the current study subjects (46%) was approximately higher than those of the previously reported values of 27% ( 26 ) and 21% ( 31 ).…”
Section: Discussionsupporting
confidence: 88%